The Readiness to Take on Family Life in Midwifery’s Student of Mercubaktijaya Padang - Widya Lestari; Desi Wildayani (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Marriage is human nature that someone will have great responsibilities in their family. But in fact, sometimes candidate bride haunted with feeling worry will happening bad things in their marriage. To prevent that, the teenager need tobe prepared before build a household. Midwife candidate is future seeds, they will becomes counselor to prepare the teenager or premarital women in building a household. The purpose of this study is to describe preparation for midwifery students of MERCUBAKTIJAYA to take on the family life. The type of this research was descriptive study. Population of this study were students of the Diploma III and Bachelor Midwifery Study Programs at STIKes MERCUBAKTIJAYA Padang, amount 143 students. Samples were taken using simple random sampling technique, totaling 97 samples. Data was collected using an online form. Data processing techniques with editing, coding, entry and cleaning steps. Data analysis used univariable analysis. There are 8 types preparation to build family, five indicators has been prepared are emosional preparation (68% able manage emotion with well, 56% capable disclose feelings ); social preparation (78% able to interact, 88% able to adaption and 91% understand the value of life); interpersonal preparation (93% have attitude patient and forgiving, 87% able to listen the others and 99% appreciate for differences in couple); Skills alive (73% able to do profession house stairs, 53% able parenting and 77% able cooperate with partner); readiness in intellectual (61% have strong in memory, 87% capable to think and catch information and 89% have desire for find out). While 3 indicators unpreparedness, they are physical preparation (20% do inspection urine, 47% consume food nutritious, 37% consuming Fe tablets, 17% consuming sour folate, 24% have got TT immunization ), mental preparation (35% know role husband wife) and financial pereparation (6% have own savings, 26% prepare career before married). Concluded that respondent has prepare emotional, social, interpersonal, skills alive to bulid a family but havenot prepared yet physical, mental dan financial. We hope that there will be a premarital program for students, setting up program for supplementary tablet, iron tablets and acid folate, and financial management training for students.